Une histoire de la recherche en sciences de Gestion : des racines oubliées aux percées actuelles - POIVRET, Cédric (Revue Internationale de Psychosociologie et de Gestion des Comportements Organisationnels, 2020)
This text is based on an interview on the history of management science given on April 11, 2019, by Armand Hatchuel, Professor of Management Science and Design Theory at MinesParisTech/PSL University, and member of the French Academy of Technologies. Four themes emerged from the analysis of the interview: the concept of “management,” the history of “managerial” thought and the authors who played a role in it, the pathologies and current breakthroughs in management science, and in conclusion some elements of the history of the Scientific Management Center of the Ecole des Mines de Paris (today, MinesParisTech/PSL University). The statements transcribed were validated by Armand Hatchuel. The footnotes were mainly provided by Cédric Poivret; some were modified by Armand Hatchuel.